-6-n=-17

Simple and best practice solution for -6-n=-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-n=-17 equation:



-6-n=-17
We move all terms to the left:
-6-n-(-17)=0
We add all the numbers together, and all the variables
-1n+11=0
We move all terms containing n to the left, all other terms to the right
-n=-11
n=-11/-1
n=+11

See similar equations:

| -38+2y-8=3(y-11) | | 4(6n+6)=-168 | | -1+2y-8=3(y-11) | | -1x+9=2x+145 | | (7−b)+(3b+2)=0 | | 1+2y-8=3(y-11) | | 1+3(5w-5)=16 | | -5x-18=-11x+30 | | -5(5+3n)+7=-6(3+8n) | | -(-16-8x)=(6x-4) | | 40+0.30x=20+0.40x | | -12x+3=2x+31 | | 14x+8=41 | | 15p-9=7p+1 | | -(-16-8x)=(6x-4 | | b/11-7b=24/11 | | 4x+2(4x-8)-4=-56 | | X+1/8x=126 | | y/10-70=-67 | | 2×5x=4x | | 10.9+3x-5=13 | | -214=5(7x+2)-3x | | (d)=25+20d | | 2x-3x+4=1 | | (4y+32)-7=15 | | -u+18=201 | | 10=v-1 | | -13.13-13.2z=-3.1z | | p/3+4=5 | | -5(x-3)=-4(x-6) | | 4.97+1.97+(x/2)=12.92 | | -3(11r+5)=3(-9r+9) |

Equations solver categories